THE ADVANCED EXPERIENCE IN THE ORGANIZATION OF THE COMBINED SYSTEMS OF THE STATE FINANCIAL CONTROL AND ITS IMPORTANCE FOR UKRAINE - О. Voronkova; V. Volenko (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The relevance of the study is determined by the need to modernize the state financial control system in Ukraine in the term of globalization and European integration processes. The normative and organizational bases of construction of the combined systems of the state financial control in the leading countries are defined. The advanced experience in the effective interaction of the state financial control bodies from different branches of the state power are systematized and analyzed. The expediency for functioning of the combined system of the state financial control with a combination of elements of parliamentary and governmental systems in Ukraine is substantiated.